Maternal Sweeteners Intake Modulates Gut Microbiota and Exacerbates Learning and Memory Processes in Adult Male Offspring - de la Garza, Ana Laura; Romero-Delgado, Bianca; Martínez-Tamez, Alejandra Mayela; Cárdenas-Tueme, Marcela; Camacho-Zamora, Bianka Dianey; Matta-Yee-Chig, Daniel; Sánchez-Tapia, Mónica; Torres, Nimbe; Camacho-Morales, Alberto (Frontiers in Pediatrics, 2022)
Background: There is increasing evidence that gut microbiota in offspring is derived in part from maternal environment such as diet. Thus, sweeteners intake including caloric or non-caloric, during perinatal period can induce gut dysbiosis and program the offspring to develop cognitive problems later in life. Objective: To determine the effect of maternal high-sweeteners intake during gestation and lactation on gut microbiota shifts in adult male offspring rats and the impact on cognitive dysfunction. Methods: Thirty-four male pups from dams fed standard diet (Control-C, n = 10), high-sucrose diet (HS-C, n = 11), high-honey diet (Ho-C, n = 8) and high-stevia diet (HSt-C, n = 5) were fed standard diet after weaning and body weight and food intake were recorded once a week for 26 weeks. Learning and memory tests were performed at week 23 of life using the Barnes maze. Fecal samples from the breastfeeding and adulthood periods were collected and analyzed by sequencing the 16S rRNA V3-V4 region of gut microbiota. Results: Maternal high-sucrose and stevia diets programmed the male offspring and changes in microbial diversity by Shannon index were observed after weaning (p < 0.01). Furthermore, maternal high-stevia diet programming lasted into adulthood. The increase of Firmicutes abundance and the decrease in phylum Bacteroidetes was significantly in HS-C and HSt-C groups. This led to an increase in the Firmicutes/Bacteroidetes index although only in HS-C group was statistically significant (p < 0.05). Of note, of the downstream gram-negative Bacteroidales and the upregulation of the gram-positive Clostridiales abundance contribute to cognitive dysfunction. Conclusion: These results suggest that dams fed a high-sucrose and stevia diets during gestation and lactation favor a deficient memory performance in adult male offspring rats through shifts gut microbiota diversity and relative abundance at several taxa.